Um olhar sobre destination wedding e turismo - Oliveira, Alani Leopisi Rodrigues (Universidade Federal de São Carlos, 2020)
The wedding events today follow strong trends in the tourism market, where the "destination wedding" is inserted, the present study brings us a vision of the tourism aspect that has great potential and also increasingly has been seen as a rising niche for tourism. The increase in demand for this type of marriage has shown that It is becoming popular. This study aims to analyse what are the determining factors for the "destination wedding". The results allow us to conclude that cultural and social factors together with proper marketing drive the decision of the destination where they will perform the wedding ceremony. Where destinations compete with each other to be the one that presents the tourist with the best resource utility, whose destination will be selected mainly from the destination marketing, the prestige of the place and also being related to the scenic beauty that the destination presents.
A look at destination wedding and tourism
Keywords: Casamento; Evento; Turismo; Destinos; Wedding; Event; Tourism; Destination; CIENCIAS SOCIAIS APLICADAS::PLANEJAMENTO URBANO E REGIONAL::SERVICOS URBANOS E REGIONAIS